Emerging Adults’ Adverse Life Events and Psychological Functioning: A Comparison Based on Intergenerational Trajectories of Child Maltreatment - Langevin, Rachel (Journal of interpersonal violence, 2023)
Intergenerational continuity of child maltreatment (CM) is a well-documented phenomenon of concern; however, its effects on the child’s level of exposure to CM, as well as subsequent trauma exposure and adult functioning remain undocumented. The present study aimed to further explore the intergenerational effects of CM by comparing emerging adults (EA; ages 18–25) on their exposure to CM, adult victimization, and psychological functioning according to their mother’s CM histories. One hundred and eighty-five mothers and their EA completed independently an online survey measuring sociodemographics, material deprivation, CM, adult victimization, and psychological functioning. The participating dyads (primarily White and female-identifying) were recruited online through social media, universities, and advertisements in non-profit organizations throughout Canada. Findings revealed that maternal histories of CM were associated with increased neglectful and physically abusive acts endured in childhood for maltreated EA. Maternal histories of CM, regardless of the EA’ victimization status, were associated with a higher EA’ number of adulthood interpersonal—but not non-interpersonal—traumas experienced. While a maternal history of CM was a risk factor for intimate partner violence (IPV) in maltreated EA, it was protective for non-maltreated EA. Maltreated EA with maltreated versus non-maltreated mothers presented more psychological difficulties, but only if they also reported material deprivation. Practitioners working with children at-risk or exposed to CM should document parents’ histories of CM and take that into account in their assessments and intervention practices. This study also provides further evidence to support social policies targeting the family system as a whole.